Copyright's arc / Martin Skladany, Penn State Dickinson Law. - Skladany, Martin (Cambridge University Press, 2020)
In Copyright's Arc, Martin Skladany rejects a one-size-fits-all copyright regime. Within developed countries, copyright's incentives have spawned multinational corporations that create a plethora of slick, hyped entertainment options that encourage Americans to overconsume, whereas in developing countries, extreme copyright blocks the widespread distribution of entertainment, which impedes women's equality and human rights movements. Meanwhile, moderate copyright in middle-income countries helps foster artistic movements that forge inclusive national identities. Given these conditions, Skladany argues that copyright should vary between countries, following an arc across the development spectrum.